KAJIAN POLA ALIRAN PADA INDUSTRI KONVEKSI DI DESA TINGKIR LOR, KECAMATAN TINGKIR - Yuliana Dhiah Taufika; Sri Rahayu (Jurusan Perencanaan Wilayah dan Kota, 2018)
Tingkir Lor Village Convection is one of the industries in Tingkir Kota Salatiga. This convection industries has been established since 1980 and still operated until now. The beginning of the convection industries in Tingkir Lor village are inseparable from the Damatex Factory's role in that year to provide wasted raw materials for free to the Tingkir Lor Village’s resident. But over time, the needs of raw materials increase and require various materials that can not be fulfilled by the convection industries in the goods and services sector. The requirements of these needs will make a connection with other areas to fulfilled these needs. The needs are including the flow of goods and services in the form of raw materials, supplementary raw materials, labor and marketing of convection products. The data analysis is based on three aspects in flow pattern of convection industries, such as input, process, and output. Data analysis used in this research is quantitative descriptive analysis that obtained from questionnaires, interviews and documentations by examining the flow patterns of goods and services within the convection industries. The results of data assessment shows that convection industries in Tingkir Lor village have two patterns of goods and services flow that is input and output aspect. The input and output aspects is the origin, destination and intensity that occur in the convection industries related to the external territory. The distribution of raw material in the Tingkir Lor village’s convection industries originally comes from Solo, Salatiga, Semarang and Ungara. As for the distribution of labor is dominated from the internal area of the convection industries. The production process in Tingkir Lor village’s convection industries still occurs in the internal area, causing no flow patterns that can be connected and formed. Convection products in Tingkir Lor Village are dominated by products such as pants, bed sheets, bed cover and clothing with a sale price ranged between Rp 5.000 up to Rp 300.000 depends on the products sold from each of the convection industries. Sales of convection industries in Tingkir Lor village have reached some regions in Indonesia such as Salatiga, Solo, Semarang, Yogyakarta, Pekalongan, Kalimantan, Sumatra, Bali and Papua.